Uczestnictwo rodziny w procesie profesjonalnego kształcenia muzycznego dziecka - Kędzia, Marta (Pedagogika Społeczna Nova, 2024)
The author, expressing interest in the subject of the family’s position in the process of professional musical education of a child, creates a background for the narration by exploring selected threads related to the specificity of professional music education and understanding space in its special family dimension. Taking up the above issues and placing them within the framework of theoretical inquiries is an invitation to discussion, and the shading of certain areas regarding the participation of the family in the specialist education of the child opens the way to further research extended to the topic of the family’s cultural capital and its importance in the educational choices of a musically gifted child.